Singapore Method for Teaching Basic Operations with Fractional Numbers in Eight Levels Students - Niño-Vega, Jorge Armando; López-Sandoval, Diana Patricia; Mora-Mariño, Eduar Ferney; Torres-Cuy, María Alejandra; Fernández-Morales, Flavio Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper presents a classroom experience aiming to the improvement of solution capability for daily problems with fractional numbers. The work was done under the qualitative research-action approach, the sample was formed by 35 students of the eight grade from a Colombian school. The diagnostic shows that the majority of students ignore concepts related to fractional numbers, doesn’t know the basic operations and doesn’t apply them in context. The classroom performed three activities: delicious pizza, drawing fractions and I have-you have, which start from a concrete material, passing through the graphic representation, and ending with the manipulation of the abstract concept. After the intervention, the students achieved the skills related to representation and operation with fractional numbers. It can be concluded that the Singapore method is appropriate to teach mathematical concepts, because beginning with a concrete object, the student knowledge assimilation is easier.